The Effect of Service Recovery Performance on Word of Mouth with the Mediation of Perceived Justice and Complaint Handling Satisfaction among Bpjs Ketenagakerjaan Participants - Fahrizal, Doni; Sumarwan, Ujang; Noor Yuliati , Lilik (Asian Journal of Social and Humanities, 2026)
This study aims to analyze the effect of service recovery performance (SRP) on word of mouth (WOM) with perceived justice (PJ) and complaint handling satisfaction (CHS) as mediating variables. The research employs an explanatory quantitative approach, involving participants who had previously submitted complaints through the comment section of BPJS Ketenagakerjaan’s official Instagram account. Data were collected using a Likert-scale questionnaire and analyzed using structural equation modeling with partial least squares. The results show that SRP has a significant effect on PJ, CHS, and WOM. The strongest effect occurs in the relationship between SRP and PJ, indicating that fast responses, clear explanations, and empathetic interactions enhance participants’ perceived justice. SRP also increases CHS. CHS shows a direct but weak effect on WOM, indicating that cognitive satisfaction alone may not be sufficient to encourage participants to recommend the service. The mediation analysis reveals that PJ significantly mediates the relationship between SRP and WOM, while CHS does not serve as a direct mediator. These findings emphasize that emotional and procedural fairness plays a more decisive role in generating positive WOM than satisfaction with the complaint-handling process itself. Thus, perceived justice emerges as a key psychological factor influencing participants’ communication behavior. This study provides important implications for BPJS Ketenagakerjaan, highlighting the need to strengthen digital complaint-handling performance by improving response speed, clarity of information, empathetic communication, and procedural consistency. These efforts are essential to building perceived justice, enhancing participant trust, and fostering positive WOM in digital environments.